Donor Selection and Management - Snell, Gregory I.; Paraskeva, Miranda; Westall, Glen P. (Seminars in Respiratory and Critical Care Medicine, 2013)
This article reviews recent developments in the selection, assessment, and management of the potential lung donor, which aim to increase donor organ use. The scarcity of suitable donor organs continues to limit lung transplantation, but the situation is changing. An expanded donor pool, including the now widespread use of donation after cardiac death (DCD) lungs; the use of extended donor lungs; and the ability of ex vivo lung perfusion (EVLP) to evaluate and improve donor lungs are key initiatives. These strategies have substantially lifted donor lung utilization rates from historically low levels of less than 15% to rates greater than 50%. Indeed, since 2004 there has been an accelerated year-on-year increase in the number of lungs transplanted globally. Intermediate-term studies are now confirming that long-term outcomes are not being significantly compromised and that more individuals with terminal, symptomatic lung disease are being transplanted. It is now quite clear that many of the historical factors used to define a lung as “extended” do not actually produce significantly inferior outcomes. There has been a dramatic increase in research and clinical interest in donor lung assessment, management, and novel therapeutic strategies. The lessons learned are now being applied widely beyond the lung as researchers aim to increase availability and optimize other solid organs for transplantation.
Keywords: lung transplantation; donation after cardiac death; ex vivo lung perfusion; organ donor; donor management